Endothelium-dependent and -independent hepatic artery vasodilatation is not impaired in a canine model of liver ischemia-reperfusion injury - Miranda,L.C. (2007)
We investigated whether hepatic artery endothelium may be the earliest site of injury consequent to liver ischemia and reperfusion. Twenty-four heartworm-free mongrel dogs of either sex exposed to liver ischemia/reperfusion in vivo were randomized into four experimental groups (N = 6): a) control, sham-operated dogs, b) dogs subjected to 60 min of ischemia, c) dogs subjected to 30 min of ischemia and 60 min of reperfusion, and d) animals subjected to 45 min of ischemia and 120 min of reperfusion. The nitric oxide endothelium-dependent relaxation of hepatic artery rings contracted with prostaglandin F2a and exposed to increasing concentrations of acetylcholine, calcium ionophore A23187, sodium fluoride, phospholipase-C, poly-L-arginine, isoproterenol, and sodium nitroprusside was evaluated in organ-chamber experiments. Lipid peroxidation was estimated by malondialdehyde activity in liver tissue samples and by blood lactic dehydrogenase (LDH), serum aspartate aminotransferase (AST) and serum alanine aminotransferase (ALT) activities. No changes were observed in hepatic artery relaxation for any agonist tested. The group subjected to 45 min of ischemia and 120 min of reperfusion presented marked increases of serum aminotransferases (ALT = 2989 ± 1056 U/L and AST = 1268 ± 371 U/L; P < 0.01), LDH = 2887 ± 1213 IU/L; P < 0.01) and malondialdehyde in liver samples (0.360 ± 0.020 nmol/mgPT; P < 0.05). Under the experimental conditions utilized, no abnormal changes in hepatic arterial vasoreactivity were observed: endothelium-dependent and independent hepatic artery vasodilation were not impaired in this canine model of ischemia/reperfusion injury. In contrast to other vital organs and in the ischemia/reperfusion injury environment, dysfunction of the main artery endothelium is not the first site of reperfusion injury.